High Level Sub-Saharan Africa NARES - CGIAR meeting on Genetic Innovation, Nairobi 27-28 June 2022 - Aide Memoire - Das, Biswanath (CGIAR, 2022)
A high-level meeting between leaders from NARES in Sub-Saharan Africa, SROs (ASARECA, CCARDESA, CORAF), development partners and CGIAR Genetic Innovation took place on 27-28 June 2022 at the Trademark Hotel in Nairobi, Kenya.